2016
DOI: 10.1016/j.ipej.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

P-wave dispersion: an update

Abstract: P-wave dispersion (PWD, Pd or Pdis) is a noninvasive electrocardiographic (ECG) marker for atrial remodeling and predictor for atrial fibrillation (AF). PWD is defined as the difference between the widest and the narrowest P-wave duration recorded from the 12 ECG leads. Increased P-wave duration and PWD reflect prolongation of intraatrial and interatrial conduction time with lack of a well-coordinated conduction system within the atrial muscles, with inhomogeneous, asynchronic, pro-inflammatory and anti-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 61 publications
(72 reference statements)
4
67
1
2
Order By: Relevance
“…We can assume that the prolonged PWD rather than LA size is more critical in predicting AF recurrence. The prolonged PWD may be as a result of other pathologies such as conduction delay, inflammation, fibrosis, excessive reactive oxygen species, downregulation of ion channels, and gap junctions (which may also trigger arrhythmias) that might not be accurately reflected by LA size (Pérez‐Riera et al, ; Sovari, ).…”
Section: Discussionmentioning
confidence: 99%
“…We can assume that the prolonged PWD rather than LA size is more critical in predicting AF recurrence. The prolonged PWD may be as a result of other pathologies such as conduction delay, inflammation, fibrosis, excessive reactive oxygen species, downregulation of ion channels, and gap junctions (which may also trigger arrhythmias) that might not be accurately reflected by LA size (Pérez‐Riera et al, ; Sovari, ).…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting results are still reported regarding the values obtained for P‐wave duration in several experimental models . Other P wave features such as P wave dispersion rather than P wave duration might also be useful to detect atrial abnormalities such as increased dispersion of refractoriness, fragmented impulse propagation, atrial dilatation, and fibrosis which promote slow and inhomogeneous atrial conduction . Censi et al.…”
Section: Discussionmentioning
confidence: 95%
“…Wu et al showed that IAB in SR and CHADS 2 score independently and synergistically predicted new‐onset AF (Wu et al, ). A positive predictive accuracy of 79% in separating patients with PAF from control subjects has been reported with ECG measurement of PWD using a P maximum value of 106 ms (Pérez‐Riera et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the YZ P‐rep and the ElAngSpeed P‐rep are indices of delayed activation of the LA (i.e. IAB; Conte et al, ; Jurkko et al, ; Pérez‐Riera et al, ; Tse et al, ), however, it is not possible at the moment to exclude or quantify a concomitant effect of atrial repolarization abnormality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation